Sequence table method for the solution of pneumatic and hydraulic circuits. - Henao Castañeda, Édison de Jesús; Monroy Jaramillo, Mauricio (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
This article presents the sequence table method, used for solving motion sequences in pneumatic and hydraulic using basic skills. This method is a useful tool for teaching and for the industry because it provides a solution in an organized and systematic manner. Equations that relate inputs and outputs are obtained from the sequence table, as well as memories are used to avoid the interference of signals. The equations are simplified in order to achieve optimal results that can be implemented with basic pneumatics or electro-pneumatics. These equations allow the simulation of the design to be done with electronic sequential logic.